Pengaruh Disiplin Kerja dan Semangat Kerja terhadap Kinerja Pegawai pada Kantor SAMSAT Kota Palopo - Suryati Suryati; Khairunnisa Edy; Lyravirna Lyravirna; Feby Ceisy Nadya; Rika Yusuf (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the influence of work discipline and work enthusiasm on employee performance at the SAMSAT Office of Palopo City. The background of this research stems from the importance of improving employee performance to support the effectiveness and efficiency of public services, especially in government agencies that provide direct services to the community. One of the efforts to improve employee performance is to understand and pay attention to internal factors such as work discipline and work enthusiasm. Work discipline involves adherence to rules, responsibility in completing tasks, and punctuality. Meanwhile, work enthusiasm reflects the motivation, enthusiasm, and commitment of employees toward their duties. Both of these factors are believed to significantly influence the productivity and quality of employees’ work. This research uses a quantitative approach with an associative method. The population in this study consists of all 40 employees of the SAMSAT Office of Palopo City, and the sampling technique used is total sampling. Data were collected through questionnaires and analyzed using multiple linear regression to test the simultaneous and partial effects of the independent variables on the dependent variable. The F-test was used to determine the simultaneous effect, the t-test for partial effects, and the coefficient of determination (R²) to measure the contribution of the independent variables to the dependent variable. The results show that work discipline and work enthusiasm simultaneously have a significant effect on employee performance (significance value = 0.001). However, partially, only work enthusiasm has a significant effect on performance (significance value = 0.004), while work discipline does not show a significant effect (significance value = 0.148). The coefficient of determination of 43.6% indicates that the two independent variables explain nearly half of the variance in employee performance. These findings highlight the importance of enhancing work enthusiasm through increased motivation, performance appreciation, and the creation of a positive work environment.